2021
DOI: 10.3390/ijms221910702
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Microgravity Inhibits Rodent Dermal Fibroblastic Differentiation of Mesenchymal Stem Cells by Suppressing ERK/β-Catenin Signaling Pathway

Abstract: Studies have shown that bone marrow-derived mesenchymal stem cells (BMSCs) can differentiate into dermal fibroblasts to participate in skin-repairing. However, at present, little is known about how microgravity affects dermal fibroblastic differentiation of BMSCs in space. The aim of this study was to investigate the effect of simulated microgravity (SMG) on the differentiation of BMSCs into dermal fibroblasts and the related molecular mechanism. Here, using a 2D-clinostat device to simulate microgravity, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Thompson et al, our previous work demonstrates that the expression and nuclear translocation of TAZ, a paralog of YAP, is downregulated by SMG which is responsible for the inhibition of osteogenic differentiation of mesenchymal stem cells (Chen et al 2015(Chen et al , 2016. In this study, we showed that the YAP expression and nuclear translocation are suppressed in derma fibroblasts by SMG treatment, which has not been reported yet.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Thompson et al, our previous work demonstrates that the expression and nuclear translocation of TAZ, a paralog of YAP, is downregulated by SMG which is responsible for the inhibition of osteogenic differentiation of mesenchymal stem cells (Chen et al 2015(Chen et al , 2016. In this study, we showed that the YAP expression and nuclear translocation are suppressed in derma fibroblasts by SMG treatment, which has not been reported yet.…”
Section: Discussionsupporting
confidence: 45%
“…To simulate microgravity in vitro, a 2D rotation clinostat was used as we reported previously (Cheng et al, 2021). The clinostat was developed by the National Microgravity Laboratory, Institute of Mechanics, Chinese Academy of Sciences, which allows a maximum of four chambers to rotate simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…Yang et al demonstrated that ERK phosphorylation induced by IL-17RB increased β-catenin expression and promoted lung cancer metastasis 31 . ERK is an vital upstream regulator of the β-catenin signaling pathway 32 , its activity may be suppressed following treatment with antitumor drugs or the downregulation of oncogenes 33 - 35 . In the current study, the expression of β-catenin was highly expressed in patients with ANP32A-high CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial MSCs were further substantiated, as progenitors of endometrial fibroblasts, to differentiate into these endometrial stromal fibroblasts ( Spitzer et al, 2012 ; Barragan et al, 2016 ). Previous in vitro studies also showed that fibroblastic differentiation of human adipose-derived MSCs (AD-hMSCs) was enhanced by bone morphogenetic protein-4 treatment under hypoxic culture conditions ( Lui et al, 2021 ) and that dermal fibroblast differentiation of bone marrow MSCs was inhibited by suppressing ERK/β-catenin signaling ( Cheng et al, 2021 ). Still, TGF-β could induce fibroblast differentiation of lung resident MSCs in vitro ( Chen et al, 2016 ).…”
Section: Mesenchymal Stem/stromal Cells In Contribution To Progressiv...mentioning
confidence: 99%